Fragile X protein controls neural stem cell proliferation in the Drosophila brain. - Callan, M.A.; Cabernard, C.; Heck, J.; Luois, S.; Doe, C.Q.; Zarnescu, D.C. (Human Molecular Genetics, 2010)
Fragile X syndrome (FXS) is the most common form of inherited mental retardation and is caused by the loss of function for Fragile X protein (FMRP), an RNA-binding protein thought to regulate synaptic plasticity by controlling the localization and translation of specific mRNAs. We have recently shown that FMRP is required to control the proliferation of the germline in Drosophila. To determine whether FMRP is also required for proliferation during brain development, we examined the distribution of cell cycle markers in dFmr1 brains compared with wild-type throughout larval development. Our results indicate that the loss of dFmr1 leads to a significant increase in the number of mitotic neuroblasts (NB) and BrdU incorporation in the brain, consistent with the notion that FMRP controls proliferation during neurogenesis. Developmental studies suggest that FMRP also inhibits neuroblast exit from quiescence in early larval brains, as indicated by misexpression of Cyclin E. Live imaging experiments indicate that by the third instar larval stage, the length of the cell cycle is unaffected, although more cells are found in S and G2/M in dFmr1 brains compared with wild-type. To determine the role of FMRP in neuroblast division and differentiation, we used Mosaic Analysis with a Repressible Marker (MARCM) approaches in the developing larval brain and found that single dFmr1 NB generate significantly more neurons than controls. Our results demonstrate that FMRP is required during brain development to control the exit from quiescence and proliferative capacity of NB as well as neuron production, which may provide insights into the autistic component of FXS.